AVALIAÃ‡ÃƒO DO DANO PRODUZIDO PELO ÃCARO ð˜”ð˜°ð˜¯ð˜°ð˜¯ð˜ºð˜¤ð˜©ð˜¦ð˜ð˜ð˜¶ð˜´ ð˜µð˜¢ð˜¯ð˜¢ð˜«ð˜°ð˜¢ (Bondar, 1938) NA CULTURA DA MANDIOCA (ð˜”ð˜¢ð˜¯ð˜ªð˜©ð˜°ð˜µ ð˜¦ð˜´ð˜¤ð˜¶ð˜ð˜¦ð˜¯ð˜µð˜¢ Crantz), EM CRUZ DAS ALMAS, BAHIA - Farias, Alba Rejane Nunes; Bellotti, Anthony Charles; Zem, Antonio Carlos; Flechtmann, Carlos H. W. (REVISTA DE AGRICULTURA, 2020)
AVALIAÃ‡ÃƒO DO DANO PRODUZIDO PELO ÃCARO ð˜”ð˜°ð˜¯ð˜°ð˜¯ð˜ºð˜¤ð˜©ð˜¦ð˜ð˜ð˜¶ð˜´ ð˜µð˜¢ð˜¯ð˜¢ð˜«ð˜°ð˜¢ (Bondar, 1938) NA CULTURA DA MANDIOCA (ð˜”ð˜¢ð˜¯ð˜ªð˜©ð˜°ð˜µ ð˜¦ð˜´ð˜¤ð˜¶ð˜ð˜¦ð˜¯ð˜µð˜¢ Crantz), EM CRUZ DAS ALMAS, BAHIA